Natural history of intracholecystic papillary neoplasm (ICPN): a rare case of ICPN whose natural history was closely followed by ultrasound - Daisuke Koike; Hiroyuki Kato; Yukio Asano; Masahiro Ito; Satoshi Arakawa; Norihiko Kawabe; Masahiro Shimura; Chihiro Hayashi; Takayuki Ochi; Kenshiro Kamio; Toki Kawai; Hironobu Yasuoka; et al. (BMC Gastroenterology, 2022)
Abstract The natural history of intracholecystic papillary neoplasm (ICPN), especially the speed of growth from small benign to a carcinomatous lesion, is quite unrevealed. Here, we report an extremely rare case of ICPN, in which the papillary lesion was observed transforming from small and benign to malignant using abdominal ultrasound (AUS) over 2 years during routine health checks. A 44-year-old man underwent a routine health check-up. The initial AUS showed a small sessile polyp in the gallbladder, which enlarged slightly at the next AUS, a year later. In the third year, the polypoid lesion enlarged markedly, with a maximum diameter of 10 × 9 × 7 mm. Therefore, a laparoscopic cholecystectomy was performed. Microscopically, the 10 mm tumor had intracytoplasmic mucus, and a clear cytoplasm compatible with gastric-type features. Immunohistochemical analysis showed positive staining of atypical cells for MUC6 and PAS. These findings led to the diagnosis of ICPN with high-grade intraepithelial neoplasia of the gastric type. In conclusion, sessile polyps with rapid growth might be a crucial finding in the early stage of ICPN.